THE IMPORTANCE OF ROOMS OF MULTIFUNCTIONAL RESOURCES IN THE EDUCATIONAL SYSTEM OF PALMS. - Sandra Rodrigues Santos (Travessias, 2014)
ABSTRACT: The present work makes an approach on the importance of rooms of multifunctional Resources in the Educational System of Palms. The study of the object highlights issues that are inherent in the teaching-learning of students with Special Needs, i.e. , students with Disabilities, pointing out the importance of the existence of such environment pedagogically structured and thought to this target audience, the relatives and teachers involved with the students cited are also supported and helped overcoming its limitations in support of these students there in the classroom in Regular Education. Moreover, this study seeks to show that the halls of Multifunctional Resources are essential for the full development of these students and expand each day these rooms is the goal of the Ministry of Education in the entire National Territory and the Tocantins every year search meet this goal. So the people with disabilities as well as the other, which also need opportunities to develop their potential. Based on this research has been the confidence that the development of actions that bring together the public sphere and the society will allow the person with disabilities conquest your right to work, their financial independence, self-realization and social integration.